Delivering authentic arts education - Judith Dinham (South Melbourne, Victoria : Cengage, 2020)
This market-leading practical text helps student teachers develop their confidence, understanding and skills to effectively and authentically teach arts. With a strong balance between theory and practice, Delivering Authentic Arts Education outlines the true nature of arts education and its importance in the curriculum, emphasising the arts as forms of creative activity, meaning-making and expression in a cultural context. Chapters discuss how to recognise and build on your existing artistic abilities and pedagogical skills, how to encourage children's creativity, how to lead arts appreciation experiences, and the general principles of planning and assessment. Part 2 specifically examines the five arts areas: dance, drama, media arts, music and visual arts. The final part of the text, Units of Inquiry, contains valuable sample learning activities and resources that demonstrate how to plan an effective lesson within a unit of inquiry
Keywords: Art Study and teaching (Higher); Student teachers